The Romantic Age in Russian Literature - Poetic and Esthetic Norms An Anthology of Original Texts (1800-1850) - Neuhäuser, Rudolf (Slavistische Beitraege, 1975)
The Anthology is intended to provide such a systematic and analitical compendium of original texts, so as to afford some insight in the poetic, stylistic, and conceptual norms which determined the nature and evolution of literature during the first half oft the 19th century.